2014
DOI: 10.1590/bjft.2014.011
|View full text |Cite
|
Sign up to set email alerts
|

Uso de microfiltração para melhoria da qualidade e extensão da vida de prateleira de leite pasteurizado

Abstract: A microfiltração é uma das tecnologias utilizadas para melhorar a qualidade do leite fluido. O objetivo dessa revisão é abordar o uso da microfiltração do leite para estender sua vida de prateleira. A importância da qualidade do leite cru (microorganismos contaminantes e enzimas naturais do leite, provenientes das células somáticas ou do crescimento dos microrganismos psicrotróficos) e as condições de estocagem do leite cru (refrigeração), que são decisivas para a qualidade e vida de prateleira do leite pasteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(50 reference statements)
0
2
0
2
Order By: Relevance
“…This behaviour can be also confirmed in Figure 2, where the main resistance is the reversible resistance, which is related to the retention and deposition of this solid on the membrane surface, resulting in a higher concentration of this solute on the membrane surface in comparison with the bulk solution (Mello, 2012). Benedetti et al 2015and Antunes (2014) studied the nanofiltration of tofu whey and pasteurized milk, respectively, and reported that the presence of substances with high molar mass (such as proteins) can influence membrane selectivity due to the adsorption and deposition of these compounds on the membrane surface. This deposition could change the charge of the membrane, affecting the permeation of negatively or positively charged compounds.…”
Section: Concentration Of the Skim Milkmentioning
confidence: 99%
“…This behaviour can be also confirmed in Figure 2, where the main resistance is the reversible resistance, which is related to the retention and deposition of this solid on the membrane surface, resulting in a higher concentration of this solute on the membrane surface in comparison with the bulk solution (Mello, 2012). Benedetti et al 2015and Antunes (2014) studied the nanofiltration of tofu whey and pasteurized milk, respectively, and reported that the presence of substances with high molar mass (such as proteins) can influence membrane selectivity due to the adsorption and deposition of these compounds on the membrane surface. This deposition could change the charge of the membrane, affecting the permeation of negatively or positively charged compounds.…”
Section: Concentration Of the Skim Milkmentioning
confidence: 99%
“…A pasteurização é um procedimento fundamental para a eliminação dos agentes patogênicos do alimento, tornando-o um produto inócuo, alterando o mínimo possível a sua qualidade nutricional, química e sensorial (Antunes, 2014), sendo dessa forma essencial para garantir a seguridade microbiológica dos produtos lácteos disponíveis comercialmente. Uma das formas de controle da pasteurização baseia-se na detecção da enzima fosfatase, que pode indicar tanto falhas no processo térmico quanto fraude por adição do leite cru ao pasteurizado, tratando-se de um teste físico-químico grande interesse na prática rotineira de laticínios (Brasil, 2006(Brasil, , 2011.…”
Section: Introductionunclassified
“…O leite é por sua composição considerado um dos alimentos mais completos em condições nutricionais e fundamentais para dieta humana, mas pela mesma razão, estabelece um excelente substrato para o desenvolvimento de uma grande diversidade de microrganismos, inclusive os patogênicos (Closs et al, 2012). O leite é um ambiente propício para o crescimento de inúmeros microrganismos devido a sua formação rica em carboidratos, proteínas e gorduras combinados com o seu pH próximo da neutralidade (Antunes, 2014). O elevado número de microrganismos vivos no leite PUBVET Doi: 10.31533/pubvet.v14n5a572.1-4 cru denota a presença de falhas nos métodos de manipulação, higienização e sanidade do animal, sendo capaz de afetar a qualidade e reduzir a vida útil do produto final (Nörnberg et al, 2009).…”
Section: Introductionunclassified